A case of dysgraphia induced by sertraline and a review of official spontaneous adverse reaction databases. (21st January 2016) - Gentili, M.; Marinaccio, P. M.; Galimberti, C.; Carnovale, C.; Antoniazzi, S.; Pozzi, M.; Clementi, E.; Viganò, C.; Radice, S.
Summary: What is known and objectives: The occurrence of dysgraphia after sertraline intake has never been reported. The objective was to describe a case of this adverse drug reaction and present a review of similar cases held in international databases with a discussion of the possible pharmacological mechanisms. Case summary: We observed a 60‐year‐old man who experienced resting tremors, dyskinesia and dysgraphia 2 months after a stepwise increase in sertraline dosing from 50 to 200 mg/day. What is new and conclusion: Dysgraphia is a possible adverse drug reaction to sertraline, and we suggest that inhibition of extrapyramidal dopaminergic activity might be the pharmacological mechanism. Abstract : Dysgraphia, is a pathological state classified within the extrapyramidal isorders, due to the brain dysfunction induced by dementia, Parkinson's disease, delirium or medications acting on neurons. To date no similar report exists in the literature; this is the first report on an association between dysgraphia and sertraline administration. The damage or reduced neurotransmission to the extrapyramidal system induced by sertraline may explain dysgraphia.